From N-heterocyclic imine to N-heterocyclic boryloxy derived main group species - Loh, YK (2019)
In this thesis titled “From N-Heterocyclic Imine to N-Heterocyclic Boryloxy Derived Main Group Species”, we present in a series of four chapters, an overarching theme regarding the transformation of the well-known N-heterocyclic imine (NHI) ligand to its isoelectronic N-heterocyclic boryloxy (NHBO) counterpart, and their employment to tame unprecedented main group species.